2020
DOI: 10.1111/cas.14691
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of homeodomain‐interacting protein kinase 2 promotes oral squamous cell carcinoma metastasis through inhibition of P53‐dependent E‐cadherin expression

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…For instance, HIPK2 is expressed at low levels in oral squamous cell carcinoma, and low expression of HIPK2 promotes the invasion of tumour cells and metastasis of cervical lymph nodes. Mechanistically, E-cadherin expression is triggered by mediating P53, which directly targets the CDH1 (encoding E-cadherin) promoter[ 32 ]. In colorectal cancer, the percentage of HIPK2-positive cells increases with tumour progression, is significantly associated with tumour lymph node metastasis stage and is associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, HIPK2 is expressed at low levels in oral squamous cell carcinoma, and low expression of HIPK2 promotes the invasion of tumour cells and metastasis of cervical lymph nodes. Mechanistically, E-cadherin expression is triggered by mediating P53, which directly targets the CDH1 (encoding E-cadherin) promoter[ 32 ]. In colorectal cancer, the percentage of HIPK2-positive cells increases with tumour progression, is significantly associated with tumour lymph node metastasis stage and is associated with worse prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer, HIPK2 was downregulated in tumor tissues and its suppression enhanced cell metastasis 25 . Depletion of HIPK2 expression had been shown to promote oral squamous cell carcinoma cell metastasis 26 . It had been reported that LINC00261 repressed pancreatic cancer glycolysis and growth by increasing HIPK2 level via targeting miR-222-3p 27 .…”
Section: Discussionmentioning
confidence: 99%
“…E-cadherin expression is known to be regulated by both transcriptional and post-translational mechanisms [ 12 , 15 ]. In tumor cells, p53 can transcriptionally promote E-cadherin expression by directly targeting the CDH1 (coding E-cadherin) promoter [ 38 ] or indirectly reducing DNMT1-mediated CDH1 promoter methylation [ 10 , 11 ]. However, we found that cisplatin-induced p53 activation led to loss of E-cadherin in RPTCs.…”
Section: Discussionmentioning
confidence: 99%